Antigen Processing and Remodeling of the Endosomal Pathway: Requirements for Antigen Cross-Presentation - Compeer, Ewoud B.; Flinsenberg, Thijs W.; van der Grein, Susanna G.; Boes, Marianne (Frontiers in Immunology, 2012)
The cross-presentation of endocytosed antigen as peptide/class I MHC complexes plays a central role in the elicitation of CD8+ T cell clones that mediate anti-viral and anti-tumor immune responses. While it has been clear that there are specific subsets of professional antigen presenting cells (APC) capable of antigen cross-presentation, description of mechanisms involved is still ongoing. Especially amongst dendritic cells (DC), there are specialized subsets that are highly proficient at antigen cross-presentation. We here present a focused survey on the cell biological processes in the endosomal pathway that support antigen cross-presentation. This review highlight DC-intrinsic mechanisms that facilitate the cross-presentation of endocytosed antigen, including receptor-mediated uptake, recycling and maturation including the sorting of membrane proteins, dynamic remodeling of endosomal structures and cell-surface directed endosomal trafficking. We will conclude with description of pathogen-induced deviation of endosomal processing, and discuss how immune evasion strategies pertaining endosomal trafficking may preclude antigen cross-presentation.